Periodic approximations of homogenization problems. (25th May 2012) - Pankov, Alexander; Xu, Steve Yongzhi
<x xml:space="preserve">Abstract</x> We show that any non‐periodic nonlinear elliptic homogenization problem can be approximated by periodic homogenization problems. Copyright © 2012 John Wiley & Sons, Ltd.